Romanian-American Negotiations in Education, Science, Culture, and Arts - MIHALY, Roxana; ANDRAȘ, Sonia D.; SIGMIREAN, Cornel (2023)
As a political model for the young democracy in interwar Romania,as a protector against threats to the sovereignty and integrity of the state, asa cultural model, and as a daily life, America represented for Romania areference point, a factor of stability and progress. America was a model andally of the civilized world!Unfortunately, isolated in the interwar period from the political realitieson the continent, America saw how, at the end of the ‘30s, the politicalcreation of the Paris Peace Conference collapsed, the US being invited to“abandon jazz” to enter a new war on the European continent, extendedto Asia and Africa, to save civilization, alongside the UK. At the war’s end,Eastern Europe fell victim to communist totalitarianism imposed by theUSSR, and its peoples were forced to abandon the Western model ofcivilization in favor of the communist model. However, after 45 years ofcommunism, the American model became negotiable again as a cultural,economic, and political model for Romanians, allowing us to reconstructessential pages in the history of interwar Romania in the context of Romanian-American relations.